Profitability, Firm Size, and Liquidity as Determinants of Firm Value: Evidence from Indonesia’s Textile and Garment Sector - Sangadji, Nursania; Hermuningsih, Sri; Rinofah, Risal (Universitas Muhammadiyah Semarang, 2025)
This study examines the effect of profitability, firm size, and liquidity on firm value in textile and garment manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using a purposive sampling method, the study selects companies that meet specific criteria, resulting in a sample analyzed through multiple linear regression. Profitability is measured using Return on Assets (ROA), the natural logarithm of total assets represents firm size, and liquidity is assessed through the Current Ratio (CR). In contrast, firm value is measured using the Price-to-Book Value (PBV) ratio. The results indicate that profitability does not significantly affect firm value, suggesting that investors consider other financial factors when assessing a company's worth. Firm size negatively and significantly affects firm value, implying that larger firms may experience inefficiencies that reduce their attractiveness to investors. Liquidity also does not significantly impact firm value, reinforcing that holding excess liquid assets does not necessarily contribute to higher firm valuation. However, when tested simultaneously, profitability, firm size, and liquidity collectively significantly impact firm value, indicating their interconnected role in financial decision-making. The findings align with agency, trade-off, and signalling theories, providing new insights into the valuation of firms in emerging markets. The study offers practical implications for corporate managers, emphasizing the importance of optimizing asset utilization and balancing financial strategies to enhance firm value. Additionally, the study highlights the need for investors to consider multiple financial indicators beyond traditional metrics.